Tinjauan Hukum Islam Terhadap Implementasi Peraturan Pemerintah Nomor 60 Tahun 2016 di Polres Konawe Selatan - Nur Husna Sukri; Ipandang Ipandang; Muh. Idris (Institut Agama Islam (IAIN) Kendari, 2021)
This study aims to find out Islamic Law in Government Regulation Nomos 60 of 2016 concerning Types and Tariffs of Non-Tax State Revenue Applicable to the Indonesian National Police at the Konsel Police. Konsel has complied with the applicable rules regarding the procedure for depositing PNBP. The second PNBP has not been implemented optimally because violations are still found, such as SIM makers not taking the exam test, the registration queue is irregular, and there are still illegal levies. Third, in terms of Islamic law, the PNBP process is in accordance with Islamic law, especially regarding the procedures for depositing PNBP but its implementation has not been maximized and even violations are found that are contrary to the principles of justice (QS. An-Nisa 135) and the principle of equality (QS Al-Hujurat 13).